Legal Working Paten di Indonesia Berdasarkan TRIPs: Perbandingan India dan Sri Lanka - Irfan Dwi Syahroni (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2021)
Article 20(2) of the 2016 Patent Law provides more clarity that such implementation must support technology transfer, absorption of investment, and/or provision of employment opportunities. However, Article 20 of the Patent Law is no longer in line with current developments, in which among countries in Southeast Asia, only Indonesia applies local working. The local working policy is currently a concern because it requires patent holders to work on patents locally. The local working policy requires that the patent recipient produce the patented product or apply a patented process in the country of the patent issuer. Therefore, this article seeks to stipulate that the Patent Law, which requires local working, will not conflict with the TRIPs Agreement. Considering India and Sri Lanka, this article looks at several aspects of implementing local working policies. In India, in the Patents Act 1970, the Indian approach required local patent work, leading to compulsory licenses in cases where the conditions were not met. In other words, it grants a compulsory license for failure to work under Article 31 of the TRIPs. Sri Lanka implemented a local working policy to overcome the potential disadvantages of the lack of a coherent legislative framework to facilitate local patent work. It benefits from modifying its current approach to compulsory licensing. With this comparative study, the Indonesian government can introduce local working requirements and processes to domestic patents while still paying attention to the public interest. KEYWORDS : Patent, Local Working, TRIPs Agreement.